2022
DOI: 10.3390/molecules27134192
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics, Antioxidant and Hypoglycemic Activities of Polysaccharide from Siraitia grosvenorii

Abstract: The structural characterization, the in vitro antioxidant activity, and the hypoglycemic activity of a polysaccharide (SGP-1-1) isolated from Siraitia grosvenorii (SG) were studied in this paper. SGP-1-1, whose molecular weight is 19.037 kDa, consisted of Gal:Man:Glc in the molar ratio of 1:2.56:4.90. According to the results of methylation analysis, GC–MS, and NMR, HSQC was interpreted as a glucomannan with a backbone composed of 4)-β-D-Glcp-(1→4)-, α-D-Glcp-(1→4)-, and 4)-Manp-(1 residues. α-1,6 linked an α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Compared to studies on the components of SG, relatively little research has been done on SG polysaccharide (SGP). 2,5,10,11 Recently, our group has focused on the isolation and purification of SGP, its structure, hypoglycemic and antioxidant properties, and bioavailability. 2,5,11 We have obtained two SGP polysaccharides in successive isolations, mannoglucan (M w = 19.04 kDa, Gal:Man:Glc = 1:2.56:4.90) and glucan (M w = 23.40 kDa, Glucan).…”
Section: ■ Bioactive Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to studies on the components of SG, relatively little research has been done on SG polysaccharide (SGP). 2,5,10,11 Recently, our group has focused on the isolation and purification of SGP, its structure, hypoglycemic and antioxidant properties, and bioavailability. 2,5,11 We have obtained two SGP polysaccharides in successive isolations, mannoglucan (M w = 19.04 kDa, Gal:Man:Glc = 1:2.56:4.90) and glucan (M w = 23.40 kDa, Glucan).…”
Section: ■ Bioactive Compoundmentioning
confidence: 99%
“…The Dietary Supplement Health and Education Act (DSHEA) of 1994, published by the U.S. Food and Drug Administration (FDA), defines a dietary supplement as a product designed to augment the diet, potentially including a range of ingredients such as food extracts, concentrates, metabolites, or combinations is known for its sweet flavor and low-calorie profile . It exhibits several health benefits like anti-inflammatory properties, lung purification, phlegm removal, liver and intestinal function regulation, blood sugar reduction, antiaging, and prevention of neurodegenerative diseases. The effectiveness of SG primarily stems from its rich composition of active elements, such as polysaccharides and sweet glycosides, making it an excellent candidate for dietary supplements.…”
Section: Introductionmentioning
confidence: 99%
“…It contains α- and β-glycosidic bonds and is elucidated as a glucomannan with a backbone composed of 4) -β-D-Glcp- (1→4) -, α-D-Glcp- (1→4) -, and 4) -Manp- (1 residue. α-1,6 linked an α-D-Galp branch, and α-1,6 linked an α-D-Glcp branch) [ 59 ]. The polysaccharide structure from S. grosvenorii is shown in Figure 6 [ 60 ].…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Recent evidence from the literature revealed that polysaccharides from different plant species could inhibit α-glucosidase activity [ 88 , 122 , 151 ]. A polysaccharide fraction, AXA-1, isolated from wheat bran showed a potential non-competitive mode of inhibitory effects against the α-glucosidase enzyme [ 123 ].…”
Section: Plant-derived Bioactive Compounds As Potential α-Glucosidase...mentioning
confidence: 99%